The disappeared : remnants of a dirty war - Ferguson, Sam (Attorney) (Book collections on Project MUSE., 2023)
"The Disappeared: Remnants of a Dirty War tells the remarkable saga of one country's attempt to right the wrongs of an unspeakably dark past. Using one of the most recent war crime trials as his lens, Sam Ferguson relates how and why Argentina decided to prosecute its aging Dirty Warriors a generation after the collapse of its last corrupt military regime"--